Synthesis and Characterization of Activated Carbon from Biowaste-Peanut Shell and Application to Preconcentration/Removal of Uranium - Yaman, Mehmet; Demirel, Maruf Hursit (Springer, 2021)
This study aims to synthesize and characterize an economical and ecological adsorbent with high adsorption capacity. For this purpose, the peanut shells (Pistacia vera L.) were modified chemically. After the synthesis of activated carbon (AC), the optimum conditions for enrichment steps were performed using parameters: pH and contact time for uranium in the model solutions. The measurements were carried out by inductively coupled plasma-mass spectrometry (ICP-MS). From the shapes of the BET isotherms, the AC obtained exhibits type I. The study indicated that the surface area and total pore volume of the AC were found to be 679.9 m(2) g(-1) and 0.31 cc g(-1), respectively. The adsorption capacity was found to be 260 mg g(-1). The optimum pH was found to be 6.0 for enrichment using the AC obtained by sulfuric acid as a chemical-modifier. The optimized method was applied to enrichment of U at ppb levels in the model solutions.
Keywords: Enrichment; Activated carbon; Uranium; ICPMS; Characterization; Peanut shells